Study of Savy Metal Concentrations in the Industrial Waste Effluents - Mehta, B.H.; Churi, A.J. (Asian Journal of Chemistry, 2012)
The concentration of twelve different heavy metals in the waste effluents were studied, namely As, Cd, Pb, Cu, Zn, Mo, V, Ni, Hg, Se, Cr and Mn. Wste effluents were collected from different locations around various chemical industries. Samples were collected at regular interval of two months, during day time. Each samples were analysed for heavy metal concentration using standard methods and by ICP-AES technique at RSIC, I.I.T., Mumbai.